Treatment of Ankyloglossia with Carbon Dioxide (CO2) Laser in a Pediatric Patient - Chiniforush, Nasim; Ghadimi, Sara; Yarahmadi, Nazli; Kamali, Abbas (Journal of Lasers in Medical Sciences, 2012)
INTRODUCTION: Laser surgery as an alternative for conventional surgical procedure has gained special attention. Using Carbon Dioxide (CO2) laser has some benefits like less post-operative pain, swelling and infection, decrease in risk of metastasis and edema, and less bleeding providing dry sites for surgery. CASE REPORT: A 12 years old boy with lingual frenum with indication for excision was referred to the laser department of Tehran University of medical sciences dental school. CO2 laser was used with 10600 nm wavelength, 1.5 W output power, 100 Hz frequency and 400 μsec pulse duration in non-contact mode. RESULTS: The result of using CO2 laser was dry and bloodless field during operation, no post operative swelling, no pain or discomfort, with normal healing process. CONCLUSION: We suggest and stimulate the use of CO2 laser for soft tissue surgery because of elimination of suture, convenient coagulation, time saving, patients’ comfort and easy manipulation.